KERAGAMAN GENETIK POPULASI KAYU MERAH (Pterocarpus indicus Willd) MENGGUNAKAN PENANDA RAMDOM AMPLIFIED POLYMORPHISM DNA - Purnamila Sulistyawati; AYPBC Widyatmoko (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
Kayu merah ( Pterocarpus indicus Willd) which listed as one of the IUCN Red List of Threatened Species in the category Vulnerable (VU A1D) is naturally distributed throughout Indonesia included Java, Sulawesi, Maluku, Bali, East Nusa Tenggara, West Nusa Tenggara and Papua. Random Amplified Polymorphic DNA (RAPD) molecular markers have been used to analyze the genetic diversity of six (6) natural populations of kayu merah from Seram Island, Manggarai Timur-Flores, Ngada-Flores, Soe-Timor Tengah Selatan, Kefamenanu-Timor Tengah Utara and Kupang. Ninety-nine (99) polymorphic loci were obtained from twelve RAPD primers. The mean of genetic diversity was 0.2024. Population with the highest genetic diversity was Soe (0.2925) and the lowest genetic diversity was Ngada (0.1212). The highest genetic distance among the populations was between Ngada and Kefamenanu (0.376), while the nearest genetic distance was between Ngada and Manggarai Timur (0.060). The informations resulted from this study are important to support the tree improvement and conservation programme of kayu merah.